PENGEMBANGAN MASYARAKAT PADA PELAKU USAHA INDUSTRI ABON IKAN GABUS BERBASIS WEB DI KEL.BONTOPARANG KEC.PARANGLOE KAB.GOWA - Indra, Dolly; Nurhayati, Lilis (Jurnal BALIRESO, 2018)
Community development is a process in empowering individuals and groups of people byproviding skills they need to bring positive changes within their own communities. Communitydevelopers should understand both how to work with individuals and to influence communitiesposition in terms of larger social institutions. Several problems encountered in BontosungguNeighborhood,Sub-district of Bontoparang, are lack of understanding on the importance ofmarketing of their products, lack of facilities or media to market the products made, no increase incommunity welfare, less creative work partners in marketing, the absence of Online BasedInformation System for marketing. The program focus on facilitating by counseling, simulationand training for the SMEs (Small to Medium-sized Enterprise) by creating prosperouscommunities who are able to market their products via online-based information system services inBontosunggu Neighborhood, Sub-district of Bontoparang, District of Parangloe, Gowa Regency.The outreach is to gain an online-based training module of entrepreneurship management inproduct marketing. Partners are able to be self-supporting in marketingimplementation. Software:Web Application for Marketing Information Systems, Articles are in the media.